新加坡华语中英语码转换的特征和因素 ： 以综艺节目为例 = A study on code-switching in Singapore local variety shows - 林靖怡 Lim, Jing Yi (2015)
在新加坡这样一个多元种族、文化和语言的国家，语码转换是新加坡人日常对话里频繁出现的语言现象。本文以综艺节目为语料探讨新加坡华人语码转换的特点，以语码转换所涉及的词类为分析重点，并讨论影响语码转换的可能因素，如性别、说话对象的身份等。本文发现新加坡华人最常使用句内语码转换，而名词，动词和形容词是最常被语码转换的对象，而交际用语也经常出现于语码转换。从性别角度来看，本文语料发现女性语码转换频率比男性低。此外，成年人的语码转换也因他们说话的对象人数和年龄不同而不同。In a multi-racial, multi-culture and multi-language country like Singapore, code-switching (CS) can be widely observed in everyone’s daily conversation. With data from Singapore local variety shows, this project explores the characteristic of CS in Singapore Chinese, including the part of speech of the words that frequently appear in CS and the possible factors (e.g., the speaker’s gender and the listener’s identity) that may affect CS. This project finds that Singaporean Chinese most frequently use intra-sentential switching; in addition, nouns, verbs, and adjectives occur in CS most frequently. As for the factors of CS, females tend to code-switch less frequently than male speakers. Also, the CS of an adult speaker varies according to the number or age group of the listeners.